Pollution Haven Hypothesis in Africa: Does the Quality of Institutions Matter? - Bouzahzah, Mohamed (International Journal of Energy Economics and Policy, 2022)
This article aims at investigating whether the FDI inflows affect CO2 emissions for a set of 40 African countries. To be specific, it seeks to perceive, to what extent the quality of institutions plays a role in the empirical validity of the famous pollution haven hypothesis (PHH). We apply Panel ARDL and the three estimators; Pooled Mean Group (PMG), Mean Group (MG) and Dynamic Fixed Effect estimator (DFE) but also Granger causality and Dumitrescu and Hurlin causality for annual data from 1988 to 2016. Long run results indicate the link between FDI, and pollution is relatively complex. If in general, the PHH does not seem to be validated, the result represents quite the opposite when we consider the institutional quality in the diverse African countries. Indeed, our results show the quality of institutions determines the nature of FDI received by African countries. In countries with a high level of corruption, inward FDI significantly reduces CO2 emissions, while in countries with low institutional quality, inward FDI increases CO2 emissions. Some policy recommendations have been formulated to support African countries reduce carbon emissions and support economic development. In particular, institutional reform would enable African countries to reconcile economic development, particularly through the FDI, with environmental quality.